The Case for Intermittent Carbapenem Dosing in Stable Haemodialysis Patients - Vanda Ho; Felecia Tay; Jia En Wu; Lionel Lum; Paul Tambyah (MDPI AG, 2020)
Purpose: Antimicrobial resistant infections are common in patients on haemodialysis, often needing long courses of carbapenems. This results in a longer hospital stay and risk of iatrogenic complications. However, carbapenems can be given intermittently to allow for earlier discharge. We aim to describe the clinical outcomes of intermittent versus daily meropenem in stable, intermittently haemodialysed patients. Methods: In total, 103 records were examined retrospectively. Data collected include demographics, clinical interventions and outcomes such as hospital length of stay (LOS), 30-day readmission rates and adverse events. Findings: Mean age 61.6 ± 14.2 years, 57.3% male. Most common bacteria cultured were Klebsiella pneumoniae (16.5%). The most common indication was pneumonia (27.2%). Mean duration of therapy on meropenem was 12.4 ± 14.4 days; eight patients needed more than 30 days of meropenem. In total, 55.3% did not have intervention for source control; 86.4% received daily dosing of meropenem; 7.8% patients received intermittent dosing of meropenem only, and 5.8 patients received both types of dosing regimens. LOS of the index admission was shorter for the intermittent arm (15.5 ± 7.6 days versus daily: 30.2 ± 24.5 days), though 30-day readmission was higher (50% versus daily: 38.2%). Implications: We recommend further rigorous randomised controlled trials to investigate the clinical utility of intermittent meropenem dosing in patients on stable haemodialysis.